Clinical Significance of Screening Electrocardiograms for the Administration of Propranolol for Problematic Infantile Hemangiomas. (24th February 2021) - Phillips, James D.; Merrill, Tyler; Gardner, J. Reed; Thomas Collins, R.; Sanchez, Jenika; Johnson, Adam B.; Eble, Brian K.; Hartzell, Larry D.; Kincannon, Jay M.; Richter, Gresham T.
Abstract : Objective . Low-dose nonselective β blockade is an effective treatment for problematic infantile hemangioma (PIH). Screening electrocardiograms (ECG) are performed prior to the initiation of propranolol to minimize the risk of exacerbating undiagnosed heart block. How ECG results affect subsequent propranolol usage and patient management remains unclear. We examined the value of ECG prior to propranolol therapy in a quaternary pediatric hospital. Methods . A retrospective chart review was performed on all infants who received propranolol (2 mg/kg/day divided three times daily) to treat PIH at Arkansas Children's Hospital from Sept. 2008 to Sept. 2015. All available demographic, historical, and clinical data were obtained. ECGs and echocardiographic data were reviewed and summarized. A pediatric cardiologist read all ECGs. Results . A total of 333 patients (75% female) received propranolol therapy. ECG information was available for 317 (95%). Abnormal findings were present on 44/317 (13.9%) of study ECGs. The most common abnormal finding was "voltage criteria for ventricular hypertrophy" (n = 35, 76.1%). Two patients had abnormal rhythms; one had first-degree atrioventricular (AV) block, and one had occasional premature atrial contractions. Of the 31 patients who underwent echocardiograms, 20 (35%) were abnormal. 2.9% of infants with PIH treated with propranolol required a follow-up with a cardiologist. No patient was precluded from taking propranolol due to the findings on screening ECG. Conclusions . Screening ECGs prior to propranolol therapy are abnormal in nearly 14% of patients with PIH but are unlikely to preclude therapy. In the absence of prior cardiac history, this cohort offers further evidence suggesting that screening ECGs may be of limited value in determining the safety of propranolol in otherwise healthy infants with PIH.